1995
DOI: 10.1192/bjp.167.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug-Induced Dysphoria

Abstract: While dysphoria is a well-recognized reaction in healthy volunteers, it is probably insufficiently recognised in patients, particularly if it occurs in the absence of akathisia. Better detection could improve compliance in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 14 publications
5
38
0
5
Order By: Relevance
“…From our data, in line with proposals from King et al (1995), it would appear that there was some dissociation between these two conditions, in that all subjects recognised an inner restlessness, whereas only half the sample reported dysphoria. In addition, among subjects reporting dysphoria there appeared to be a number of dierent processes leading to what may be substantially dierent experiences coded under a common rubric.…”
Section: Discussion These Results Have Implications For a Number Of Dsupporting
confidence: 89%
See 2 more Smart Citations
“…From our data, in line with proposals from King et al (1995), it would appear that there was some dissociation between these two conditions, in that all subjects recognised an inner restlessness, whereas only half the sample reported dysphoria. In addition, among subjects reporting dysphoria there appeared to be a number of dierent processes leading to what may be substantially dierent experiences coded under a common rubric.…”
Section: Discussion These Results Have Implications For a Number Of Dsupporting
confidence: 89%
“…dose to volunteers produced no restlessness or other eects during the subsequent hour and a half as measured using visual analogue rating scales. The dierences between their ®ndings and both ours and those of King et al (1995) may stem from a number of sources. One possibility is that intravenous preparations of haloperidol or other compounds might produce a quite dierent side eect pro®le to oral preparations; there is some evidence in support of this.…”
Section: Discussion These Results Have Implications For a Number Of Dmentioning
confidence: 91%
See 1 more Smart Citation
“…EPS are extremely worrying and stigmatizing for patients. Moreover, they are accompanied by emotional [43] and cognitive disturbances [44] and are liable to give rise to tardive dyskinesia [45] . With this in mind, we had better evaluate the actual risks of EPS in an index like the number needed to harm, rather than cling to the apparently simple distinction between 'typicals' and 'atypicals'.…”
Section: Resultsmentioning
confidence: 99%
“…One study in normal volunteers (King et al, 1995) demonstrated that dysphoria often occurs in the absence of motor restlessness and can thus be underdiagnosed. It is possible that some patients with schizophrenia presenting with depressive symptoms may in fact be troubled by antipsychoticinduced dysphoria, without the associated motor aspects of akathisia that make the diagnosis more obvious.…”
Section: The Role Of Antipsychotic Medicationmentioning
confidence: 99%